Tropheryma whipplei Detection by Nanopore Sequencing in Patients With Interstitial Lung Disease - Guo, Yifan; Li, Lijuan; Li, Zhenzhong; Sun, Lingxiao; Wang, Hui (Frontiers in Microbiology, 2021)
Tropheryma whipplei is a bacterium associated with Whipple’s disease, which commonly manifests as weight loss, arthralgia, and diarrhea. The most frequently involved organs comprise the heart and eyes, in addition to the central nervous system. Few studies have explored the relationship between T. whipplei and pneumonia. Herein, we report three patients with interstitial lung disease (ILD) of unknown cause, whose bronchoalveolar lavage fluid (BALF) were evaluated via Nanopore sequencing. In our in-house BALF Nanopore platform, human DNA was removed with saponin, to improve the reads ratio of microorganisms/host. T. whipplei was the sole or most abundant pathogen in all the patients, comprising 1,385, 826, and 285 reads. The positive result was confirmed via quantitative polymerase chain reaction (PCR) with two pairs of primers (cycle threshold value: 33.26/36.29; 31.68/32.01; 28.82/28.80) and Sanger sequencing. To our knowledge, this is the first report of T. whipplei detection using Nanopore-based sequencing. The turnaround time was approximately 6–8 h in clinical laboratories, including less than 1 h for analysis. In conclusion, the results of this study confirm that Nanopore sequencing can rapidly detect rare pathogens, to improve clinical diagnosis. In addition, diagnosis of Whipple’s disease should be combined other laboratory findings, such as periodic acid-Schiff (PAS) staining, and considered a possibility in middle-aged men presenting with ILD and a clinical history of unexplained arthralgia and/or fever.